Importance of Dental Records in Disaster Victim Identification - Afşin, Hüseyin; Karadayı, Beytullah (The Bulletin of Legal Medicine, 2014)
Due to the fact that teeth are more resistant to physical and external factors (burn, decay, trauma etc.) than the other parts of the body, they can be used in identification practices more efficiently. Mass fatality incidents have been occurred frequently in Turkey due to earthquakes, floods, landslides, airplane crashes, fires, industrial accidents, terrorist attacks and gun fights. Identification of victims after natural or unnatural disasters is a difficult and time consuming process. Specialists who are trained in forensic dentistry field, take part in groups formed for disaster victim identification. One of the primary and most important practices of forensic dentistry is the identification of bodies which have no relations to identify or are deformed greatly, after a mass fatality. In this field, techniques based on the comparison of dental records have come into prominence. The objective of this article is to give practical information regarding the usage of dental records in mass fatalities. Keywords: Forensic dentistry, Mass fatalities, Identification, Antemortem dental records, Postmortem dental records.